Efficacy of a Single Dose of Pregabalin on Signs of Anxiety in Cats During Transportation—A Pilot Study - Lamminen, Terttu; Korpivaara, Mira; Suokko, Minna; Aspegrén, John; Palestrini, Clara; Overall, Karen (Frontiers in Veterinary Science, 2021)
Objectives The aim of this clinical pilot study was to evaluate dosage, efficacy and clinical safety of a single oral dose of pregabalin in cats that experience fear and anxiety when placed into a carrier and transported by car. Methods Thirteen client-owned cats were enrolled in a blinded, randomized, crossover study with 3 treatment days approximately one week apart. The cats were assigned to receive pregabalin oral solution at dosages of 5 and 10 mg/kg, and placebo in a randomized order, one treatment per week. Treatment was administered approximately 90 minutes before placing the cat into a carrier and starting transportation. Efficacy was assessed by the owners using a categorical scale and, based on video recordings, by an external observer, both blinded to the treatment. Results Owners assessed that cats given pregabalin displayed less vocalization, restlessness and panting during transportation than did cats given placebo. Correlation between owners’ and external observer’s assessment of the overall treatment effect was good (0.63, p <0.01), which confirms the owners’ ability to observe reliably their own cat’s behavior. Transient mild ataxia was the most common adverse event reported. The human commercial formulation used in this study was found difficult or very difficult to administer by 79% of the owners. Conclusions and relevance Based on results of this pilot study, a single oral dose of pregabalin was well tolerated, and decreased signs of anxiety and fear associated with car transportation in cats, as evaluated by blinded owners and external observer. Use of pregabalin prior to travelling may increase cat welfare and compliance for transportation. Further studies are needed to investigate use of oral pregabalin in cats to alleviate signs of anxiety and fear associated with transportation and sequelae, like veterinary visits, and to develop a more user-friendly formulation.